A Study of Solid-Liquid Extraction with HF And HNO3 as Solvent for Determination of Cr and Cu in the River Sediment near the Muria Nuclear Power Plant - Imelda Fajriati; Malawati Rizkiyah; Muzakky Muzakky (Jurnal ILMU DASAR, 2011)
A Study of solid-liquid extraction for determination of Cr and Cu in the river sediment near the Muria Nuclear Power Plant has been studied. The river sediment assayed is in Kancilan, Balong, Suru, Dombang, and Wareng rivers. A study of solid liquid extraction focus on the optimum condition of extraction such as: concentrations of HF and HNO3 as are solvent, the extraction time, the accurate of this method; and comparing HF+ HNO3 solvent ability with HNO3 4N + HCl 0.7N and HCl 0.5N in extracting Cr and Cu in the river sediment. Determination of Cr and Cu concentration uses Atomic Absorpton Spectrometry. The research result shows that the optimum condition of extraction obtained in HF and HNO3 concentrations is 40% and 65% v/v respectively; and the extraction time is 5 hours. This research method shows good accuracy that is 84.810 % and 102.461 % for Cr and Cu respectively. In comparing the solvent ability to extract metal, it is obtained that HF 40% + HNO3 65% solvent is the best solvent in Cr metal extraction, whereas HNO3 4N + HCl 0.7N solvent is the best solvent in Cu metal extraction from the river sediment sample.